Trends in the Incidence and Management of Acute Myocardial Infarction From 1999 to 2008: Get With the Guidelines Performance Measures in Taiwan - Lee, Cheng‐Han (J Am Heart Assoc, 2014)
BACKGROUND: The American Heart Association Get With the Guidelines (GWTG) program has improved care quality of acute myocardial infarction (AMI) with important implications for other countries in the world. This study evaluated the incidence and care of AMI in Taiwan and assessed the compliance of GWTG in Taiwan. METHODS AND RESULTS: We used the Taiwan National Health Insurance Research Database (1999–2008) to identify hospitalized patients ≥18 years of age presenting with AMI. The temporal trends of annual incidence and care quality of AMI were evaluated. The age‐adjusted incidence of AMI (/100 000 person‐years) increased from 28.0 in 1999 to 44.4 in 2008 (P<0.001). The use of guideline‐based medications for AMI was evaluated. The use of dual antiplatelet therapy (DAPT) increased from 65% in 2004 to 83.9% in 2008 (P<0.001). Angiotensin‐converting enzyme (ACE) inhibitor or angiotensin receptor blocker (ARB) was used in 72.6% in 2004 and 71.7% in 2008 (P=NS) and β‐blocker was used in 60% in 2004 and 59.7% in 2008 (P=NS). Statin use increased from 32.1% to 50.1% from 2004 to 2008 (P<0.001). The in‐hospital mortality decreased from 15.9% in 1999 to 12.3% in 2008 (P<0.0001). Multivariable analysis showed that DAPT, ACE inhibitor/ARB, β‐blocker, and statin use during hospitalization were all associated with reduced in‐hospital mortality in our AMI patients. CONCLUSIONS: AMI incidence was increasing, but the guideline‐based medications for AMI were underutilized in Taiwan. Quality improvement programs, such as GWTG, should be promoted to improve AMI care and outcomes in Taiwan.